2006
DOI: 10.1128/jb.188.5.1882-1891.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Heterologous Siderophores Ferrioxamine B and Ferrichrome Activate Signaling Pathways inPseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa secretes two siderophores, pyoverdine and pyochelin, under iron-limiting conditions. These siderophores are recognized at the cell surface by specific outer membrane receptors, also known as TonB-dependent receptors. In addition, this bacterium is also able to incorporate many heterologous siderophores of bacterial or fungal origin, which is reflected by the presence of 32 additional genes encoding putative TonB-dependent receptors. In this work, we have used a proteomic approach to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
223
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(231 citation statements)
references
References 61 publications
4
223
0
4
Order By: Relevance
“…P. aeruginosa strains have w30 genes encoding TonB-dependent receptors (TBDRs), which are involved in the uptake of ferrisiderophores (Cornelis & Bodilis, 2009). Receptors for mycobactin and carboxymycobactin (Llamas et al, 2008), ferrichrome and ferrioxamine (Llamas et al, 2006;Cuív et al, 2007;Hannauer et al, 2010), rhizobactin, aerobactin and schizokinen (Cuív et al, 2006), and vibriobactin (Elias et al, 2011) have all been identified. Given the evidence to date, P. aeruginosa appears to have the greatest capacity for siderophore piracy in the CF lung microbiome.…”
Section: Siderophore-mediated Iron Acquisitionmentioning
confidence: 99%
“…P. aeruginosa strains have w30 genes encoding TonB-dependent receptors (TBDRs), which are involved in the uptake of ferrisiderophores (Cornelis & Bodilis, 2009). Receptors for mycobactin and carboxymycobactin (Llamas et al, 2008), ferrichrome and ferrioxamine (Llamas et al, 2006;Cuív et al, 2007;Hannauer et al, 2010), rhizobactin, aerobactin and schizokinen (Cuív et al, 2006), and vibriobactin (Elias et al, 2011) have all been identified. Given the evidence to date, P. aeruginosa appears to have the greatest capacity for siderophore piracy in the CF lung microbiome.…”
Section: Siderophore-mediated Iron Acquisitionmentioning
confidence: 99%
“…citrate (Cox, 1980b;Harding & Royt, 1990)]. While outer-membrane receptors for most of these heterologous siderophores have been identified (Banin et al, 2005;Cuiv et al, 2006;Ghysels et al, 2005;Llamas et al, 2006Llamas et al, , 2008Poole et al, 1990), additional (e.g. periplasmic or inner-membrane) transport components are generally not evident from the genome sequence.…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa produces two siderophores, pyoverdine (Meyer & Hornsperger, 1978;Poole et al, 1991;Visca et al, 2007) and pyochelin Heinrichs et al, 1991;, though the organism is also able to utilize several siderophores produced by fungi and other bacteria (Cornelis et al, 1987;Cuiv et al, 2006Cuiv et al, , 2007Llamas et al, 2006Llamas et al, , 2008Meyer, 1992;Meyer et al, 1999;Poole et al, 1990), as well as additional molecules with Fe-chelating ability [e.g. citrate (Cox, 1980b;Harding & Royt, 1990)].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that P. aeruginosa has two receptors that mediate the uptake of the E. coli siderophore enterobactin, PfeA and PirA (Dean & Poole, 1993;Ghysels et al, 2005). In addition, P. aeruginosa is capable of utilizing the Mycobacterium paratuberculosis siderophore mycobactin through FemA (Llamas et al, 2008), ferrichrome through FiuA, ferrioxamine through FoxA (Llamas et al, 2006), citrate through FecA (Cox, 1980), aerobactin through ChtA (Cuív et al, 2006), and the siderophores cepabactin (Mislin et al, 2006), desferrichrysin, desferricrocine and coprogen (Meyer, 1992) through unidentified receptors. It is interesting to note that the above-mentioned receptors probably represent only a part of the total iron-acquisition potential of P. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the TonB-dependent siderophore receptor is tightly regulated by the level of iron (Noinaj et al, 2010). Furthermore, in several cases, the siderophore itself acts as a signal and induces the expression of its cognate receptor (Beare et al, 2003;Llamas et al, 2006;Neilands, 1995). The binding of the siderophore to its receptor induces the expression of various genes, including genes required for siderophore uptake, and can be regulated through several regulatory pathways.…”
Section: Introductionmentioning
confidence: 99%